WAYS TO INCREASE THE COMPETITIVENESS OF VITICULTURE AND WINE CLUSTERS IN UZBEKISTAN - Azadova Bonuposhsha Alisher kizi (Scholar Express Journals, 2022)
Improving the competitiveness of winemaking is a complex issue, which depends not only on producers, but also on state and regional support and regulation, the coordinated development of viticulture and winemaking in general, the scale of implementation. Each component of increasing the competitiveness of viticulture is a specific set of management, economic, marketing, legal tools, norms and methods.
Keywords: cluster; competitive; market share; import